Characterization of Fe 2 O 3 /Mn 2 O 3 oxygen carrier for chemical looping combustion prepared by dry impregnation method - Afandi N.M.; Manap A.N.A.; Mansor F.H.; Ghani M.F.A.; Kadir N.F.; Liu W. (Science Publishing Corporation Inc, 2023)
Recently, bauxite waste was found as newly sourced of Fe-based oxygen carrier in chemical looping combustion (CLC) since it contains high Fe and capable to be used as oxygen carrier at low cost. This study focuses on synthesizing and characterizing the bauxite waste that found in Malaysia with Mn 2 O 3 using dry impregnation method and study the feasibility of this bauxite waste as oxygen carrier. Results show the combination of bauxite waste - Mn 2 O 3 at 900C produces crystallite size 21 nm with the presence of Fe-Mn, stable Al 2 O 3 and Ti elements that can improve the reactivity of Fe-Mn oxygen carrier. Moreover, Al 2 O 3 that contains naturally in bauxite waste can acts as supported material for Fe-Mn oxygen carrier in order to increase performance in CLC process. Therefore, this powder was successfully synthesized using dry impregnation method at calcination temperature 900C and fit to be tested in a fluidized bed reactor to simulate the CLC process since it has smaller and stable particle size. 2018 Authors.